Analisis Faktor-Faktor yang mempengaruhi Ambulasi Dini Post ORIF pada Pasien Fraktur Femur Study Retrospektif - Giat Wantoro; Muflihatul Muniroh; Henni Kusuma (Jurnal Akademika Baiturrahim Jambi, 2020)
Femur fracture is a loss of continuity of the femur, which can be caused by direct trauma to the thigh or pathological factors. The main treatment for fractures is ORIF. Implementation of early ambulation is important to prevent post ORIF complications. Objective: This study aims to analyze the factors that influence early ambulation post ORIF  in femoral fracture patients. Methods: The study design was a cross-sectional retrospective approach with 82 respondents and data collection using medical record data. The independent variables are education, sex, age, hemoglobin, temperature, blood pressure, pain, fracture location, and time span of operation while the dependent variable is early ambulation. The test used in multivariate is logistic regression test. Results and discussion: Research shows education (p = 0,000), gender (p = 0.028), age (p = 0,000), Hb (p = 0.029), pain (p = 0.001), and location of the fracture (p = 0.007) , is an influential factor. The multivariate model found the fracture location to be the most influencing factor in post ORIF early ambulation in femur fracture patients with p = 0.023 and an OR value of 2.140. Conclusion: This study recommends that nurses first examine the factors that influence early ambulation, especially fracture location factors before providing post ORIF early ambulation interventions in femur fracture patients